Experimental study on pool two-phase flow and droplet entrainment characteristics - Yu’ang Tan; Rulei Sun; Tan Ma; Puzhen Gao; Ruifeng Tian; Sichao Tan (Annals of Nuclear Energy, 2026)

Unlocking the potential in municipal reclaimed water electrolysis for hydrogen production: Identification of the primary water matrix - Zongping Wang; Haoran Chen; Zhenbin Chen; Yunfei Li; Ang Lu; Yujie Cheng; Guosen Zhang; Ge Li; Shunjie Zhu; Lin Li; Lizhi Huang; Jiakun Fang; et al. (Water Research, 2026)

Dimensional reduction of hydrogen-bonding networks induced by hierarchical confinement to promote ultra-fast adsorption of hydrated ions to targeted sites - Meng Du; Zhiqiang Sun; Aiwen Wang; Ang Li; Jun Ma (Water Research, 2026)

Using machine learning models to estimate ecotoxicity effect factors for various nanomaterials in life cycle assessment - Xiao Li; Yuan Yuan; Ang Li; Wei Sun; Weichun Ma (Journal of Hazardous Materials, 2026)

Cajaninstilbene acid induced apoptosis and cell cycle arrest in glioblastoma multiforme through mitochondrial ROS–mediated MAPK pathways - Yong-Ang Li; Tian-Zeng Bian; Hong Li; Jia-Wen Li; Liu-Tao Ma; Hao-Di Wu; Shuai Chen; Jia-Yi Chen; Hao Zeng; You-Bing Mao; Peng Wang; Qi Qiao (Food and Chemical Toxicology, 2026)

Carrier-free nanoparticles derived from Huanglian Jiedu decoction target ATP5F1C to eliminate senescent cells and ameliorate pulmonary fibrosis - Ying Zhang; Lirun Zhou; Yajian Li; Weiling Wang; Tong Yang; Qianyu Zhang; Hechen Tang; Jiayun Guo; Ling Huang; Chen Wang; Zheng Chu; Ang Ma; et al. (Chemical Engineering Journal, 2026)

Ecological risk and source apportionment of heavy metals in surface sediments from a key shellfish production area in Northern Liaodong Bay, China - Ang Li; Suyan Xue; Muzhan Sun; Qingbin Ma; Jiaqi Li; Lulei Liu; Ling Zhu; Yuze Mao (Marine Environmental Research, 2026)

Design of functional hydrogel beads based on polysaccharide-encapsulated Ganoderma lucidum spores for stability and targeted gastrointestinal delivery of protein–spore complex - Longqin Li; Ang Ma; Jiang Ni; Ruixing Chen; Junzhe Zhang; Zipeng Gong; Hai-Ning Lyu (Carbohydrate Polymers, 2026)

Fully exposed Fe clusters activated with interfacial oxygen vacancy for accelerating catalytic ozonation of electron-deficient 1-adamantanecaboxylic acid through interfacial electronic metal-support interactions - Xuan Qu; Lu Wang; Zhi-Qiang Sun; Ang Li; Jun Ma (Chemical Engineering Journal, 2025)

Prevalence and genetic analysis of porcine circovirus type 3 (PCV3) in Henan Province of China during 2022-2024 - Lin-Lin Chen; Hao Li; Xuan-Ang Wang; Lan-Lan Zheng; Shi-Jie Ma; Hong-Ying Chen (Archives of Virology, 2025)

Experimental investigation on wave attenuation capacity of kelp farms - Yushun Lian; Jiantao Ma; Dong-ang Li; Jinhai Zheng; Aifeng Tao; Wenxing Chen; Jisheng Zhang; Solomon C. Yim (Ocean Engineering, 2025)

Molecular characterization of porcine reproductive and respiratory syndrome virus in Henan and Shanxi, China, during 2023–2024 - Tao Wang; Xuan-Ang Wang; Jia-Qi Zhang; Lan-Lan Zheng; Ping-Li Wang; Hong-Ying Chen; Shi-Jie Ma (Archives of Virology, 2025)

Impact of C-8 hydroxylation and C-7 methylglucosylation of dihydroquercetin on glucose metabolism in diabetic zebrafish larvae - Yong Cheng; Beijun Ang; Dandan Ma; Zhiwei Li; Fengxian Guo; Zhaojun Wang; Qiuming Chen; Maomao Zeng; Jie Chen; Benu Adhikari; Liduan Yin; Tong Wang; et al. (Food Bioscience, 2025)

Development and identification of porcine monoclonal antibodies against PEDV from single B cells - Xuan-ang Wang; Hong-xuan Li; Lan-Lan Zheng; Shi-jie Ma; Ping-Li Wang; Li Zhao; Hong-Ying Chen (Veterinary Immunology and Immunopathology, 2025)

Cerium oxide nanoparticles as potent inhibitors of ferroptosis: role of antioxidant activity and protein regulation - Chenran Feng; Tong Yang; Jie Zhou; Chen Wang; Zheng Chu; Ying Zhang; Junzhe Zhang; Yin Kwan Wong; Cui Liu; Peng Gao; Ang Ma; Huan Tang; et al. (Journal of Molecular Medicine, 2025)

Targeting myeloid differentiation protein 2 ameliorates rheumatoid arthritis by inhibiting inflammation and ferroptosis via MAPK and NF-κB signaling pathways - Lirun Zhou; Tong Yang; Shujie Zhang; Dandan Liu; Chenran Feng; Jiang Ni; Qiaoli Shi; Yanqing Liu; Yuqing Meng; Yongping Zhu; Huan Tang; Jigang Wang; et al. (Journal of Molecular Medicine, 2025)

Sufficient burial depth is a prerequisite for Chinese cyclina (Cyclina sinensis) to maintain normal life activities - Yurou Ma; Shiyu Yan; Zhengyu Shao; Guolong Zhou; Ang Hu; Yawei Bu; Huimin Wang; Xinqi Lv; Jianyu Liu; Yihua Chen; Zhiguo Dong (Aquaculture, 2025)

Molecular detection and genotyping of bovine viral diarrhea virus in four provinces of China - Ying Liu; Feng Zhou; Xuan-ang Wang; Xi-Meng Chen; Lan-Lan Zheng; Hong-Ying Chen; Shi-Jie Ma (Archives of Virology, 2025)

MAX-DOAS observations of pollutant distribution and transboundary transport in typical regions of China - Hongmei Ren; Ang Li; Zhaokun Hu; Hairong Zhang; Jiangman Xu; Xinyan Yang; Jinji Ma; Shuai Wang (Journal of Environmental Sciences, 2025)

Deciphering the migration of naproxen and its impact on nitrogen removal in CANON system - Xiaojing Zhang; Yujia Guo; Bingbing Ma; Ang Gao; Jiahui Nie; Chenyu Jia; Peng Zhou; Yongpeng Ma (Desalination, 2025)

High content of single-atomic sulfur in nano carbon spheres boosting potassium storage performance - Bin Cao; Zirong Guo; Huan Liu; Yu Ma; Wei Zhao; Yiheng Yang; Ang Li; Huaihe Song; Yaxiong Yang; Zhenglong Li; Wubin Du (Chemical Engineering Journal, 2025)

Role of per- and polyfluoroalkyl substances in the cardiorenal system: Unraveling crosstalk from the network of pollutants and phenotypes - Ming Yang; Jiaxin Zhao; Ziwen An; Haoran Li; Chaoying Ma; Junli Lv; Fang Xiao; Zhenzhen Tan; Longfei Li; Xiaoguang Zhang; Xuehui Liu; Yi Liu; et al. (Journal of Environmental Sciences, 2025)

Establishment of molecular weight specific chromatogram of Ganoderma glycopeptide and its application in extract - Hongjian Luo; Shuqian Lin; Zhanxi Lin; Haining Lu; Ang Ma; Dongmei Lin (Food Bioscience, 2025)

Understanding the biological identity of metal-organic framework through profiling proteomic fingerprinting of protein corona - Huan Tang; Jie Zhou; Tong Yang; Hai-Ning Lyu; Zheng Chu; Ying Zhang; Ang Ma; Junzhe Zhang; Yuqing Meng; Chong Qiu; Sheng-Tao Yang; Jigang Wang; et al. (Chemical Engineering Journal, 2025)

Kill two birds with one stone: Biochar immobilised polydopamine coated compound bacterial agent for remediation of dibutyl phthalate contaminated soil - Yue Tao; Jiaming Xu; Ang Li; Zhao Jiang; Ningyuan Ma; Rui Sun; Ying Zhang (Environmental Research, 2025)

Polylactic acid microplastics induced negative priming and improved carbon sequestration via microbial processes in different paddy soils - Liying Chen; Lanfang Han; Fayuan Wang; Qi'ang Chen; Hongkai Huang; Jie Wang; Chuanxin Ma; Ke Sun; Matthias C. Rillig; Yakov Kuzyakov; Zhifeng Yang (Soil Biology and Biochemistry, 2025)

Synthesis of nitrogen-doped crystalline Ga2O3 thin films via trimethylgallium doped NH3/H2/N2/O2 premixed stagnation flames - Lun’ang Li; Shengfeng Luo; Mengzhao Chang; Guanjie Yin; Mingchen Sun; Jingrui Ma; Xiao Wei Sun; Igor Rahinov; Bo Zhou (Fuel, 2024)

Emerging transition metal sulfide/MXene composites for the application of electrochemical energy storage - Xianghui Hu; Pin Ma; Zehao Zhang; Jian Wang; Cheng Li; Yee Sin Ang; Haibo Li; Hui Ying Yang (Chemical Engineering Journal, 2024)

Exceptional thermoelectric and mechanical performance in (Bi, Sb)2Te3 matrix facilitated by AgInSe2 alloying - Ruiheng Li; Wenxin Ou; Jianglong Zhu; Qian Deng; Xiaobo Tan; Qi Zhao; Tianbo Lu; Shaojingya Gao; Huangshui Ma; Hao Wu; Qiang Sun; Ran Ang (Chemical Engineering Journal, 2024)

Analysis of resting status reveals distinct elevational variation in metabolisms of lizards - Zhong‐Wen Jiang; Liang Ma; Shi‐ang Tao; Cheng Wenda; Chuyu Cheng; Dan‐yang Wu; Wei‐Guo Du (Ecology, 2024)
Animals spend a considerable proportion of their life span at rest. However, resting status has often been overlooked when investigating how species respond to environmental conditions. This may induce a large bias in understanding the local adaptation of species across environmental gradients and their vulnerability to potential environmental change. Here, we conducted an empirical study on montane agamid lizards, combined with mechanistic modeling, to compare elevational variations in body temperature and metabolisms (cumulative digestion and maintenance cost) between resting and active status. Our study on three populations of an agamid lizard along an elevational gradient revealed a trend of decreasing body temperature toward higher elevations, the main contributor of which was resting status of the lizards. Using population‐specific reaction norms, we predicted greater elevational variation in hourly and cumulative digestion for resting lizards than for active lizards. Climate‐change impacts, estimated as the change in cumulative digestion, also show greater elevational variation when resting status is factored into the analysis. Further, our global analysis of 98 agamid species revealed that in about half of their combined distributional range, the contribution of resting status in determining the elevational variation in cumulative digestion and maintenance cost of lizards was greater than the contribution made by a lizard's active status. Our study highlights the importance of considering resting status when investigating how species respond to environmental conditions, especially for those distributed over tropical and subtropical mountain areas.

Evaluation of characteristics on the indoor dwelling environments of traditional villages in Hehuang area of China based on basic environmental parameters under remote sensing technology - Hongbin Ma; Chengjun Jing; Ang Hu; Lihua Ma (Physics and Chemistry of the Earth, Parts A/B/C, 2024)

Dynamic monitoring of aboveground biomass in inner Mongolia grasslands over the past 23 Years using GEE and analysis of its driving forces - Dong Yang; Zhiyuan Yang; Qingke Wen; Leichao Ma; Jian Guo; Ang Chen; Min Zhang; Xiaoyu Xing; Yixin Yuan; Xinyu Lan; Xiuchun Yang (Journal of Environmental Management, 2024)

Eco-infused interfacial enhancement of the anti-biofouling activity in anion exchange membranes for electrodialysis desalination - Yuyang Yao; Yueyue Lu; Yuan Li; Yanjing Ma; Edison Huixiang Ang; Jingwen Xu; Heda Ding; Yuna Shi; Yitao Chen; Junbin Liao; Zhenlu Shen; Jiangnan Shen (Chemical Engineering Journal, 2024)

The cryptic step in the biogeochemical tellurium (Te) cycle: Indirect elementary Te oxidation mediated by manganese-oxidizing bacteria Bacillus sp. FF-1 - Yuqing Liu; Huiqing Ma; Ang Li; Haixia Pan; Xianliang Yi; Yang Liu; Jingjing Zhan; Hao Zhou (Environmental Research, 2023)

Comprehensive study on particle size distribution, MAH and PAH profiles during alkylbenzene pyrolysis - Pengcheng Zhao; Tie Li; Ang Li; Yongzhi Ma; Mingming Fang; Xinling Li (Fuel, 2023)

Per- and polyfluoroalkyl substances and the associated thyroid cancer risk: A case-control study in China - Haoran Li; Ming Yang; Jing Yang; Samuel Seery; Chaoying Ma; Yi Liu; Xiaoguang Zhang; Ang Li; Huicai Guo (Chemosphere, 2023)

Three birds, one-stone strategy for synthesis of hierarchically arrayed defective MnCo2O4@NF catalyst for photothermal preferential oxidation of CO in H2-rich streams - Ang Zhou; Xiaolin Guo; Siyi Zhong; Zi'ang Chen; Qiaoling Kang; Miaogen Chen; Dingfeng Jin; Meiqiang Fan; Renxian Zhou; Tingli Ma (Chemical Engineering Journal, 2023)

A new insight into the CaO-induced inhibition pathways on PCDD/F formation: Metal passivation, dechlorination and hydroxide substitution - Xiaoxiao Wang; Jiabao Lv; Yuxuan Ying; Yunfeng Ma; Angjian Wu; Xiaoqing Lin; Ang Cao; Xiaodong Li; Jianhua Yan (Science of The Total Environment, 2023)

Nitrogen-doped carbon confined Cu-Ag bimetals for efficient electroreduction of CO2 to high-order products - Xinyao Zou; Ang Li; Chao Ma; Zhan Gao; Baowen Zhou; Lei Zhu; Zhen Huang (Chemical Engineering Journal, 2023)

Valorization of thermally hydrolyzed sludge with clay for sintering of ceramic tiles - Lei Wen; Lin Lin; Yi-ang Fan; Yang Luo; Sheng-shou Ma; Ying Zhou; Chao Yang; Kaimin Shih; Xiao-yan Li (Science of The Total Environment, 2023)

X-ray diffraction and the symmetry of ultrathin crystalline materials between two-dimensional and three-dimensional crystals - Hengrui Ma; Qiaorong Jiang; Zi-Ang Nan; Gen Li; Yanyan Jia; Ruoxin Ning; Jia-Bao Ji; Zhenming Cao; Linzhe Lü; Huiqi Li; Sheng Dai; Haixin Lin; et al. (Science Bulletin, 2023)

Distinct responses and range shifts of lizard populations across an elevational gradient under climate change - Zhong‐Wen Jiang; Liang Ma; Chun‐Rong Mi; Shi‐Ang Tao; Fengyi Guo; Wei‐Guo Du (Global Change Biology, 2023)
Ongoing climate change has profoundly affected global biodiversity, but its impacts on populations across elevations remain understudied. Using mechanistic niche models incorporating species traits, we predicted ecophysiological responses (activity times, oxygen consumption and evaporative water loss) for lizard populations at high‐elevation (

Pollution profiles, influencing factors, and source apportionment of target and suspect organophosphate esters in ambient air: A case study in a typical city of Northern China - Ang Zhao; Chao Wei; Yue Xin; Xiaoli Wang; Qingqing Zhu; Jixing Xie; Haiyun Ma; Jianzhong Xu; Mei Wang (Journal of Hazardous Materials, 2023)

Recovery of coral cover on inshore fringing reefs following mass coral bleaching in the Philippines - Ma. Regina R. Abesamis; Julia Louise Ang; Regine C. Robles; Wilfredo Y. Licuanan (Coral Reefs, 2023)

Concave gold nano-arrows (AuCNAs) for efficient catalytic reduction of 4-nitrophenol - Ang Ma; Weiye Yang; Kunpeng Gao; Junqi Tang (Chemosphere, 2023)

Fundamental study on oxidation properties at elevated pressure of typical renewable synthetic liquid fuels through low-temperature CO2 electroreduction - Zhenyingnan Zhang; Ang Li; Zheng Ma; Zhen Huang; Lei Zhu (Fuel, 2023)

Hsa_circ_0006732 regulates colorectal cancer cell proliferation, invasion and EMT by miR-127-5p/RAB3D axis - Tao Yang; Jufeng Sun; Wei Wang; Dongsheng Li; Xianxu Yang; Ang Jia; Yinda Ma; Zhongkai Fan (Molecular and Cellular Biochemistry, 2022)

Soil moisture–atmosphere feedback dominates land N 2 O nitrification emissions and denitrification reduction - Jiayuan Liao; Qiqi Luo; Ang Hu; Wenkai Wan; Dian Tian; Jingwei Ma; Tian Ma; Hao Luo; Sheng Lu (Global Change Biology, 2022)
Soil moisture (SM) is essential to microbial nitrogen (N)‐cycling networks in terrestrial ecosystems. Studies have found that SM–atmosphere feedbacks dominate the changes in land carbon fluxes. However, the influence of SM–atmosphere feedbacks on the N fluxes changes, and the underlying mechanisms remain highly unsure, leading to uncertainties in climate projections. To fill this gap, we used in situ observation coupled with gridded and remote sensing data to analyze N 2 O fluxes emissions globally. Here, we investigated the synergistic effects of temperature, hydroclimate on global N 2 O fluxes, as the result of SM–atmosphere feedback impact on N fluxes. We found that SM–temperature feedback dominates land N 2 O emissions by controlling the balance between nitrifier and denitrifier genes. The mechanism is that atmospheric water demand increases with temperature and thereby reduces SM, which increases the dominant N 2 O production nitrifier (containing amoA AOB gene) and decreases the N 2 O consumption denitrifier (containing the nosZ gene), consequently will potential increasing N 2 O emissions. However, we find that the spatial variations of soil–water availability as a result of the nonlinear response of SM to vapor pressure deficit caused by temperature are some of the greatest challenges in predicting future N 2 O emissions. Our data‐driven assessment deepens the understanding of the impact of SM–atmosphere interactions on the soil N cycle, which remains uncertain in earth system models. We suggest that the model needs to account for feedback between SM and atmospheric temperature when estimating the response of the N 2 O emissions to climatic change globally, as well as when conducting field‐scale investigations of the response of the ecosystem to warming.

Biodiversity and degradation potential of oil-degrading bacteria isolated from sediments of hydrothermal and non-hydrothermal areas of the Southwest Mid-Indian Ocean Ridge - Haolei Shi; Jiangfeng Cheng; Wei Gao; Meng Ma; Ang Liu; Tianyi Hu; Bin Han; Li Zheng (Environmental Science and Pollution Research, 2022)

Identification of structural variation and polymorphisms of a sex co-segregating scaffold in spinach - Li’ang Yu; Xiaokai Ma; William Wadlington; Ray Ming (Plant Reproduction, 2022)

Numerical Analysis of the Water-blocking Performance of a Floor with a Composite Structure under Fluid–solid Coupling - Ang Li; Qian Mu; Li Ma; Chaoyang Liu; Shengquan Wang; Feng Wang; Lin Mou (Mine Water and the Environment, 2021)

TRIC-A regulates intracellular Ca2+ homeostasis in cardiomyocytes - Xinyu Zhou; Ang Li; Pei-hui Lin; Jingsong Zhou; Jianjie Ma (Pflügers Archiv - European Journal of Physiology, 2021)
Trimeric intracellular cation (TRIC) channels have been identified as monovalent cation channels that are located in the ER/SR membrane. Two isoforms discovered in mammals are TRIC-A (TMEM38a) and TRIC-B (TMEM38b). TRIC-B ubiquitously expresses in all tissues, and TRIC-B −/− mice is lethal at the neonatal stage. TRIC-A mainly expresses in excitable cells. TRIC-A −/− mice survive normally but show abnormal SR Ca 2+ handling in both skeletal and cardiac muscle cells. Importantly, TRIC-A mutations have been identified in human patients with stress-induced arrhythmia. In the past decade, important discoveries have been made to understand the structure and function of TRIC channels, especially its role in regulating intracellular Ca 2+ homeostasis. In this review article, we focus on the potential roles of TRIC-A in regulating cardiac function, particularly its effects on intracellular Ca 2+ signaling of cardiomyocytes and discuss the current knowledge gaps.

Construction of high-density genetic maps defined sex determination region of the Y chromosome in spinach - Li’ang Yu; Xiaokai Ma; Ban Deng; Jingjing Yue; Ray Ming (Molecular Genetics and Genomics, 2021)

Improving Education About Breast Cancer for Medical Students in China - Ang Zheng; Xinmiao Yu; Lijuan Fan; Jinfei Ma; Feng Jin (Journal of Cancer Education, 2020)

Effect of Bedding Angle and Mineral Composition on Mechanical Properties and Fracture Behavior of Phyllite Under Unloading Confining Pressures - Xiaolong Guo; Zhongsheng Tan; Xiao Wang; Ang Li; Zhongjun Ma; Yongsheng Wu (Geotechnical and Geological Engineering, 2020)

A multiobjective evolutionary optimization method based critical rainfall thresholds for debris flows initiation - Yan Yan; Yu Zhang; Wang Hu; Xiao-jun Guo; Chao Ma; Zi-ang Wang; Qun Zhang (Journal of Mountain Science, 2020)

Effects of osmotic stress on the expression profiling of aquaporin genes in the roughskin sculpin (Trachidermus fasciatus) - Qian Ma; Xinfu Liu; Ang Li; Shufang Liu; Zhimeng Zhuang (Acta Oceanologica Sinica, 2020)

Effects of osmotic stress on Na+/K+-ATPase, caspase 3/7 activity, and the expression profiling of sirt1, hsf1, and hsp70 in the roughskin sculpin (Trachidermus fasciatus) - Qian Ma; JieHua Kuang; Xinfu Liu; Ang Li; Wenrong Feng; Zhimeng Zhuang (Fish Physiology and Biochemistry, 2020)

Enhanced adsorption performance and regeneration of magnetic Fe3O4 nanoparticles assisted extracellular polymeric substances in sulfonamide-contaminated water - Shanshan Pi; Ang Li; Di Cui; Zhou Su; Lu Zhou; Fang Ma (Environmental Science and Pollution Research, 2020)

Differential responses of canopy nutrients to experimental drought along a natural aridity gradient - Wentao Luo; Xiaoan Zuo; Wang Ma; Chong Xu; Ang Li; Qiang Yu; Alan K. Knapp; Roberto Tognetti; Feike A. Dijkstra; Mai‐He Li; Guodong Han; Zhengwen Wang; et al. (Ecology, 2018)
The allocation and stoichiometry of plant nutrients in leaves reflect fundamental ecosystem processes, biotic interactions, and environmental drivers such as water availability. Climate change will lead to increases in drought severity and frequency, but how canopy nutrients will respond to drought, and how these responses may vary with community composition along aridity gradients is poorly understood. We experimentally addressed this issue by reducing precipitation amounts by 66% during two consecutive growing seasons at three sites located along a natural aridity gradient. This allowed us to assess drought effects on canopy nitrogen (N) and phosphorus (P) concentrations in arid and semiarid grasslands of northern China. Along the aridity gradient, canopy nutrient concentrations were positively related to aridity, with this pattern was driven primarily by species turnover (i.e., an increase in the relative biomass of N‐ and P‐rich species with increasing aridity). In contrast, drought imposed experimentally increased N but decreased P concentrations in plant canopies. These changes were driven by the combined effects of species turnover and intraspecific variation in leaf nutrient concentrations. In addition, the sensitivity of canopy N and P concentrations to drought varied across the three sites. Canopy nutrient concentrations were less affected by drought at drier than wetter sites, because of the opposing effects of species turnover and intraspecific variation, as well as greater drought tolerance for nutrient‐rich species. These contrasting effects of long‐term aridity vs. short‐term drought on canopy nutrient concentrations, as well as differing sensitivities among sites in the same grassland biome, highlight the challenge of predicting ecosystem responses to future climate change.

Nitrogen removal performance and microbial community of an enhanced multistage A/O biofilm reactor treating low-strength domestic wastewater - Han Chen; Ang Li; Qiao Wang; Di Cui; Chongwei Cui; Fang Ma (Biodegradation, 2018)

Nitrogen removal and microbial community shift in an aerobic denitrification reactor bioaugmented with a Pseudomonas strain for coal-based ethylene glycol industry wastewater treatment - Cong Du; Chong-Wei Cui; Shan Qiu; Sheng-Nan Shi; Ang Li; Fang Ma (Environmental Science and Pollution Research, 2017)

Membrane fluidity is involved in the regulation of heat stress induced secondary metabolism in Ganoderma lucidum - Yong‐Nan Liu; Tian‐Jun Zhang; Xiao‐Xiao Lu; Bao‐Liang Ma; Ang Ren; Liang Shi; Ai‐Liang Jiang; Han‐Shou Yu; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum has become a potential model system for evaluating how environmental factors regulate the secondary metabolism of basidiomycetes. Heat stress (HS) is one of the most important environmental factors. It was previously reported that HS could induce the biosynthesis of ganoderic acids (GA). In this study, we found that HS increased GA biosynthesis and also significantly increased cell membrane fluidity. Furthermore, our results showed that addition of the membrane rigidifier dimethylsulfoxide (DMSO) could revert the increased GA biosynthesis elicited by HS. These results indicate that an increase in membrane fluidity is associated with HS‐induced GA biosynthesis. Further evidence showed that the GA content was decreased in D9des ‐silenced strains and could be reverted to WT levels by addition of the membrane fluidizer benzyl alcohol (BA). In contrast, GA content was increased in D9des ‐overexpression strains and could be reverted to WT levels by the addition of DMSO. Furthermore, both membrane fluidity and GA biosynthesis induced by HS could be reverted by DMSO in WT and D9des ‐silenced strains. To the best of our knowledge, this is the first report demonstrating that membrane fluidity is involved in the regulation of heat stress induced secondary metabolism in filamentous fungi.

Adsorption behavior of tetracycline by extracellular polymeric substrates extracted from Klebsiella sp. J1 - Ang Li; Shanshan Pi; Wei Wei; Ting Chen; Jixian Yang; Fang Ma (Environmental Science and Pollution Research, 2016)

Prescreening, identification and harvesting of microalgae with antibacterial activity - Ang Li; Ling Zhang; Zhen-yu Zhao; Sha-sha Ma; Meng Wang; Ping-huai Liu (Biologia, 2016)

Transcriptome Sequencing of the Sweet Potato Progenitor (Ipomoea Trifida (H.B.K.) G. Don.) and Discovery of Drought Tolerance Genes - Qinghe Cao; Ang Li; Jinyang Chen; Yu Sun; Jun Tang; An Zhang; Zhilin Zhou; Donglan Zhao; Daifu Ma; Shan Gao (Tropical Plant Biology, 2016)

Lake evaporation: A possible factor affecting lake level changes tested by modern observational data in arid and semi-arid China - Yu Li; Nai’ang Wang; Zhuolun Li; Ning Ma; Xuehua Zhou; Chengqi Zhang (Journal of Geographical Sciences, 2013)

Microbial community analysis of three municipal wastewater treatment plants in winter and spring using culture-dependent and culture-independent methods - Di Cui; Ang Li; Si Zhang; Changlong Pang; Jixian Yang; Jingbo Guo; Fang Ma; Jihua Wang; Nanqi Ren (World Journal of Microbiology and Biotechnology, 2012)

Characterization of a compound bioflocculant produced by mixed culture of Rhizobium radiobacter F2 and Bacillus sphaeicus F6 - Lili Wang; Fang Ma; Yuanyuan Qu; Dezhi Sun; Ang Li; Jingbo Guo; Bing Yu (World Journal of Microbiology and Biotechnology, 2011)

Genetic Variation in Hippophae rhamnoides ssp. sinensis (Elaeagnaceae) Revealed by RAPD Markers - Kun Sun; Wen Chen; Ruijun Ma; Xuelin Chen; Ang Li; Song Ge (Biochemical Genetics, 2006)